(untitled) (Experimental biology, 2015)
In present work cDNA of Triticum aestivum gene encoding homologue of ribosomal protein S6 kinase (S6K) was isolated. Analysis of TaS6K protein revealed conservative elements in kinase domain characteristic of all S6 kinases:activation loop, hydrophobic and turn motives. It was shown that Ser-466 in C-terminal HM-motif of TaS6K is a putative site of phosphorylation by T.aestivum TOR kinase. The phosphorylation of Ser-466 TaS6K is inhibited in presence of TOR-specific inhibitor pp242 in aleuronic layer of wheat grain. Also a higher level of activated TaS6K in aleuronic cells treated with gibberellin compared to abscisic acid was observed as an indication of possible participation of TOR signaling pathway in gibberellin-activated processes during germination of wheat grain.